KAJIAN PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA (UP2K) TERHADAP USAHA ANGGOTA UP2K MELATI INDAH KELURAHAN ENOK KECAMATAN ENOK KABUPATEN INDRAGIRI HILIR - Nandha, Novriyanthi Eka Nandha Eka; Indrawati, Henny Indrawati; Haryana, Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: UP2K program is one of the programs that are focused on empowering women in the village. The purpose UP2K program is to foster and develop the activities of the family business belonging to groups or individuals so as gradually to become self-employed as well as allowing the emergence of cooperative activities. In addition UP2K also help the weak economic capital for businesses through lending activities to meet the capital requirements and reduce dependence on moneylenders to be able to help the people of the economic downturn. Indragiri Hilir, UP2K Melati Indah village Enok is one UP2K who get UP2K revolving fund. This study aims to assess the program UP2K to business success UP2K member Melati Indah Sub District of Enok Enok Indragiri Hilir. This study is expected to provide information and input materials to interested parties. Penelian method used is descriptive analysis method, to get a clearer picture and detailed based on the data obtained. The data used in this study are primary data and secondary data. Primary data is data obtained through interviews with respondents that members who receive grants from UP2K Melati Indah village Enok, while secondary data is data obtained through the data from the board UP2K Enok Melati Indah village. The results showed that the program UP2K enough to affect the business carried on by members of UP2K Melati Indah village Enok this is because many members still classified into the low income category. Keywords: production number, the number of customers, expanding the marketing area, revenue